2021
DOI: 10.1002/jeq2.20182
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus mobilization from intact soil monoliths flooded under simulated summer versus spring snowmelt with intermittent freeze–thaw conditions

Abstract: Enhanced phosphorus (P) release from flooded, anaerobic soils has been extensively studied under summer temperatures but not under cold temperatures with intermittent freeze–thaw events. We investigated the temperature and freeze–thaw effects during flooding on the release of P to floodwater from soil monoliths (15‐cm depth) collected from eight agricultural fields in Manitoba. Soil monoliths were flooded with reverse osmosis water and incubated for 56 d under simulated summer flooding (SSF; 22 ± 1 °C) or snow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
2
9
1
Order By: Relevance
“…The Eh values in the SSM treatment reached values below 100 mV around 28 DAF and declined to negative values by about 42 DAF (Figure 1a). This rapid decline in redox potential of intact soil monoliths has been previously reported with flooding of soil monoliths (Shaheen, Rinklebe, Rupp, & Meissner, 2014;Weerasekara et al, 2020). In the current study, the intensity of reduction was greater in soil monoliths from SSM-treated plots compared with monoliths from LSM-treated and control plots.…”
Section: 2supporting
confidence: 82%
See 1 more Smart Citation
“…The Eh values in the SSM treatment reached values below 100 mV around 28 DAF and declined to negative values by about 42 DAF (Figure 1a). This rapid decline in redox potential of intact soil monoliths has been previously reported with flooding of soil monoliths (Shaheen, Rinklebe, Rupp, & Meissner, 2014;Weerasekara et al, 2020). In the current study, the intensity of reduction was greater in soil monoliths from SSM-treated plots compared with monoliths from LSM-treated and control plots.…”
Section: 2supporting
confidence: 82%
“…Previous studies investigating flooding‐induced P release have shown a consistent and a substantial increase in pore water and floodwater DRP concentrations with time of flooding in most unamended soils with the exception of a few (Amarawansha et al., 2015; Jayarathne et al., 2016; Kumaragamage et al., 2019). The increase in DRP concentration with flooding and the development of anaerobic conditions have been attributed to pH changes resulting in enhanced solubility of phosphate minerals and the reductive dissolution reactions releasing adsorbed and precipitated P (Maranguit, Guillaume, & Kuzyakov, 2017; Rakotoson, Rabeharisoa, & Smolders, 2016; Weerasekara et al., 2020). In the unamended soil monoliths of the current study, however, a consistent and appreciable increase in DRP concentration was not observed in pore water, possibly due to the diffusion of released P to overlying floodwater (Amarawansha et al., 2015), whereas floodwater DRP concentrations increased by about twofold reaching a peak around 35 DAF and then decreased with further flooding time.…”
Section: Resultsmentioning
confidence: 99%
“…In the unamended treatment, during the period between 7 and 42 DAF, DRP concentrations increased 1.4-4.5-fold in porewater, and 1.8-15.3-fold in floodwater. Although P release from flooded soils is greater under warm than cold temperatures (Kumaragamage et al, 2020;Weerasekara et al, 2021), significant P release into porewater and floodwater was observed in the current study, even when average daily air temperatures were between −5˚C and 5˚C during most of the first 14 days of flooding. Moreover, the peak DRP concentrations in porewater and floodwater did not coincide with the warm/high temperatures observed between 21 and 28 DAF in almost all the soils.…”
Section: Changes In Concentrations Of Porewater and Floodwater Dissol...contrasting
confidence: 57%
“…weather.gc.ca/). These wide temperature fluctuations, which are unlike the simulated conditions used by Weerasekara et al (2021), may result in a severe reduction in soils when flooded, resulting in rapid P release to floodwater; this needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation